STUDI KEBIJAKAN PEMBANGUNAN DAERAH BERPERSPEKTIF GENDER DI KABUPATEN LAMPUNG TENGAH - Ari Darmastuti; Endry Fatimaningsih; Teuku Fahmi (SOSIOLOGI: Jurnal Ilmiah Kajian Ilmu Sosial dan Budaya, 2012)
The purpose of this study to identify barriers and opportunities in the implementation of gender mainstreaming in strategic developmentof Central Lampung regency. The approach used is a qualitative approach, using in-depth interviews, questionnaires, review of documentation, and focus group discussion (FGD). The study revealed,: (1) the implementation of the legal framework is still limited; (2) lack of commitment on the implementation of gender mainstreaming in individual and institutional levels; (3) Working Group and gender focal points have not been functioning optimally; (4) there is no gender disaggregated data as well as the mechanism of action has not been established to formulate gender- disaggregated data; (5) gender analysis tools is used on a limited basis by the Badan PP dan KB, while other agencies have not implemented this analysis tool . In addition, the study also found several factors driving the implementation of Gender Mainstreaming in Central Lampung regency, (1) the readiness of human resources to carry out gender mainstreaming in the planning, implementation ,monitoring and evaluation of development; (2) the encouragement of civil society to the government in the planning, implementation, monitoring and evaluation of development and the establishment of mechanisms to ensure the delivery of gender issues.